Wedding photograph - Mumbai Archive Project Team (Jio Institute, 2024)
Ramnath Keny had his wedding photograph taken with his wife in a Mumbai studio. Vintage photos like this offer insight into the customs and traditions of the Koli community as they modernize and adapt to new trends and changing fashion.